A modified S-DIMM+: applying additional height grids for characterizing daytime seeing profiles. Issue 2 (15th June 2018) - Wang, Zhiyong; Zhang, Lanqiang; Kong, Lin; Bao, Hua; Guo, Youming; Rao, Xuejun; Zhong, Libo; Zhu, Lei; Rao, Changhui
ABSTRACT: Characterization of daytime atmospheric turbulence profiles is needed for the design of a multi-conjugate adaptive optical system. S-DIMM+ (solar differential image motion monitor+) is a technique to measure vertical seeing profiles. However, the number of height grids will be limited by the lenslet array of the wide-field Shack–Hartmann wavefront sensor (SHWFS). A small number of subaperture lenslet arrays will lead to a coarse height grid over the atmosphere, which can result in difficulty in finding the location of strong-turbulence layers and overestimates of the turbulence strength for the measured layers. To address this problem, we propose a modified S-DIMM+ method to measure seeing profiles iteratively with decreasing altitude range for a given number of height grids; finally they will be combined as a new seeing profile, with a denser and more uniform distribution of height grids. This method is tested with simulations and recovers the input height and contribution perfectly. Furthermore, this method is applied to the 102 data-sequences recorded from the 1-m New Vacuum Solar Telescope at Fuxian Solar Observatory, 55 of which were recorded at local time between 13:40 and 14:35 on 2016 October 6, and the other 47 between 12:50 and 13:40 on 2017 October 5. A 7x7 lenslet array of SHWFS is used to generate a 16-layer height grid to 15 km, each with 1 km height separation. The experimental results show that the turbulence has three origins in the lower (0–2 km) layers, the higher (3–6 km) layers and the uppermost (≥7 km) layers.